Analisis Sistem Informasi Akuntansi Penjualan pada Ameera Cafe Sampang - Rachmawati, Ria (Assyarikah: Journal of Islamic Economic Business, 2024)
This study aims to analyze the application of accounting information systems in the sales process at Ameera Café Sampang. A good accounting information system is expected to support operational efficiency and accuracy of transaction recording, which is very important for business continuity, especially in culinary businesses such as Ameera Café. This study uses a qualitative descriptive method with a case study approach. Data collection techniques are carried out through in-depth interviews with owners, managers, and staff who are directly involved in the sales process at Ameera Café. The results of the study indicate that Ameera Café has not fully implemented an effective accounting information system, especially in terms of integration between operational procedures, accounting functions, and sales transaction documentation. The procedures applied are still manual and limited to simple transaction recording without a standardized and integrated system. The accounting function is not yet optimal in monitoring and setting aside income and costs related to the sales process, so that recording errors or inaccuracies often occur in financial reports. Documentation that should include complete and clear evidence of transactions, such as sales invoices and daily reports, has not been carried out consistently. These findings indicate an urgent need to develop and improve the accounting information system at Ameera Café, especially in terms of procedures, documentation, and the application of technology to speed up and simplify transaction recording. This study recommends that Ameera Café consider adopting a computer-based accounting information system that can integrate all aspects of the business, from recording transactions to preparing financial reports in real time and accurately. Thus, the implementation of a better information system can improve financial performance, reduce the risk of errors, and support more appropriate decision making for business management.